Introduction to social security : policies, benefits, and poverty - Ditch, John, 1952- (Routledge, 1999)
An up-to-date text on an important social policy issue that needs constant updating. Essential reading for all students on social policy and administration courses.
Keywords: Social security -- Great Britain.; Sécurité sociale -- Grande-Bretagne.; POLITICAL SCIENCE -- Public Policy -- Social Security.; Social security; Great Britain